A Role for Insulin-Like Growth Factor-I in the Regulation of Schwann Cell Survival - Daniel E. Syroid; Todd Zorick; Christophe Arbet‐Engels; Trevor J. Kilpatrick; Walter Eckhart; Greg Lemke (1999)
During postnatal development in the peripheral nerve, differentiating Schwann cells are susceptible to apoptotic death. Schwann cell apoptosis is regulated by axons and serves as one mechanism through which axon and Schwann cell numbers are correctly matched. This regulation is mediated in part by the provision of limiting axon-derived trophic molecules, although neuregulin-1 (NRG-1) is the only trophic factor shown to date to support Schwann cell survival. In this report, we identify insulin-like growth factor-I (IGF-I) as an additional trophin that can promote Schwann cell survival in vitro . We find that IGF-I, like NRG-1, can prevent the apoptotic death of postnatal rat Schwann cells cultured under conditions of serum withdrawal. Moreover, we show that differentiating Schwann cells in the rat sciatic nerve express both the IGF-I receptor (IGF-I R) and IGF-I throughout postnatal development. These results indicate that IGF-I is likely to control Schwann cell viability in the developing peripheral nerve and, together with other findings, raise the interesting possibility that such survival regulation may switch during postnatal development from an axon-dependent mechanism to an autocrine and/or paracrine one.